Clinical features and management of manic episodes in adolescents. A case review - V.E. Martin Gil; M.C. Chinchilla Moreno (European Psychiatry, 2022)
Introduction Assessment and management of bipolar disorder, and particularly manic episodes in adolescents means a challenge. The presence of comorbid disorders, and divergent interpretations of manic symptoms in the context of the adolescent natural inmaturity, can make diagnosis and treatment hard goals to achieve. The existence of juvenile specific criteria for bipolar disorder is a debate topic. This concept emerged from an attempt to solve diagnosis issues and involves a wide range of definitions for mania.